O stylu biblijnej prozy Mikołaja Reja (na podstawie "Psałterza Dawidowego") = About the biblical style of Mikołaj Rej's prose (on the basis of "Psałterz Dawidowy" ["David?s Psalter"]) - Kowalska, Danuta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article aims to present the most important features of the biblical prose of Mikołaj Rej on the basis of "David's Psalter". The subject of the analyses has not been chosen randomly, as David?s Psalter belongs to 'pure' religious texts and it refers to the tradition of free translation, grounded in Poland by the work of Walenty Wróbel. Although it was created in the beginnings of the writer?s works, this literary piece shows stylistic maturity. The analyses indicate that the style of translation is the result of Rej's conscious, artistic work, who maintained some of the features of the traditional Psalter style.
Keywords: Rej, Mikołaj (1505-1569); proza biblijna; "Psałterz Dawidowy"; styl językowy; biblical prose; "David's Psalter"; linguistic style